Calibration of multicomponent force and moment transducers using uniaxial force standard machines integrated with tilted plates. (1st September 2022) - Prato, Andrea; Borgiattino, Davide; Facello, Alessio; Mazzoleni, Fabrizio; Germak, Alessandro
Abstract: Traceability of multicomponent force and moment transducers (MCFMTs) is a metrological priority as stated within the document of future strategy 2017–2027 of the Consultative Committee of Mass and Related Quantities of Bureau International des Poids et Mesures (BIPM). In this paper, a calibration system using force standard machines (FSMs) integrated with tilted plates is described. The main advantage of this method is the possibility to apply force and moment components using existing uniaxial FSMs without the necessity to modify them or to develop specific ones. On the other hand, force and moment components cannot be fully independently applied. Expanded uncertainties of the applied side forces and moments are in the order of around 5%, acceptable for several industrial applications. A procedure for the calibration and the uncertainty assessment of MCFMTs is also provided. Calibration results, in terms of main and cross-talk sensitivities, of a six-components transducer are shown. This method is easily implementable and can be adopted to improve the current standard.